We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
67
2
avatar

https://prnt.sc/oypahp

 

andrew is wrong because he used a postive instead of a negative

 Aug 28, 2019
 #1
avatar+104686 
+1

Here you go....we need this :

 

[ x - 3 ]  [ x - (2 + 2i) ] [ x - (2 - 2i) ]  =  0

 

[x - 3 ]  [ x^2 - (2 + 2i)x - (2 - 2i)x +  (2 + 2i)(2-2i) ] = 0

 

[ x - 3 ]  [ x^2 -2x - 2ix - 2x + 2ix  + 4 - 4i^2 ]   =  0

 

[ x - 3 ]  [ x^2 - 4x + 4 + 4 ]  = 0

 

[x - 3 ] [ x^2 - 4x + 8 ]  = 0

 

[ x^3 - 4x^2 + 8x - 3x^2 + 12x - 24 ] = 0

 

x^3 - 7x^2 + 20x - 24  =  0

 

 

cool cool cool

 Aug 28, 2019
 #2
avatar
0

thank you !!!

 Aug 28, 2019

32 Online Users

avatar